Evaluation of Packaging Liners in Wooden and Plastic Crates for Handling Tomatoes - L, Dari; N, Nenguwo; Sefa V, Afari (Journal of Postharvest Technology, 2018)
Postharvest losses of tomato are high and can be attributed to a series of factors which include variety of tomato, harvest treatments, packaging materials, handling techniques, transportation and market availability. Standard wooden crates which are perceived as large (about 90%) are used in the packing and transportation of tomatoes in Ghana which often leaves produce smashed due to the size and internal surface of crates. This research was conducted using plastic crates (50, 30 kg) and wooden crates (large and improvised 30 kg) and packaging liners such as jute hessian material, perforated paper and thin latex foam was used to assess which of the treatments would preserve the fruits. From the results, all treatments had percentages of damaged and undamaged fruits at varying levels. Jute lined 30 kg plastic and paper lined wooden crates and paper lined 50 kg both plastic and wooden proofed effective in curbing losses better than the remaining treatments. The wooden 50 kg control crate however, had more damaged quantities at 55% than all treatments which had damages ranging between 20 - 50. The use of crates with adequate and suitable packing liners could reduce the quantities of damaged fruits in tomato.